Structured professional psychological judgment for assessing the risk of public danger in persons with mental disorders - O. A. Makushkina; E. V. Leurda (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2023)
The results of the approbation of the Protocol of structured professional judgment developed for the assessment of psychological factors influencing the formation of socially dangerous behavior in persons with severe mental disorders are presented. In order to determine psychometric properties and prognostic reliability, 160 patients of both sexes with persistent illegal and law-abiding behavior, average age 40 ±13 years, were examined using the Protocol. The respondents were assessed for affective rigidity, extrapunitive orientation of frustration reaction, cognitive rigidity, low self-esteem, internal locus of control, lack of empathy, egocentrism, ability to reflect on life experience. Each feature was assigned a score, the scores were summed up, the amount was compared with the threshold value. Prognostic reliability was assessed using ROC analysis (Receiver Operating Characteristics). Sensitivity and specificity were 98.1% and 88.1%, respectively. The area under the ROC curve is 0.97±0.01 with 95% CI: 0.951-0.989. The resulting model was statistically significant (p<0.001). This Protocol is not an independent tool, but serves as an addition to the methodology of Structured Risk Assessment of Dangerous Behavior (SOROP) and clinical assessment. Its integration into the risk determination procedure will ensure the implementation of a comprehensive multidisciplinary approach in making judgments about the potential public danger of the patient, will increase its objectivity and evidence.